Land Use Changes Impact Analysis to Surface Runoff in Kalibenda Village - Choirul Basyar; Muhammad Arief Budihardjo; Budi Prasetyo Samadikun (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The rainwater that reaches the ground will enters the soil (infiltration) and some water are not absorbed by the soil will become surface runoff. The regional development tends to change water catchment areas by changing land functions and affecting surface runoff. The regional development in Kalibenda Village has cause problems related to the local community water supply. In 2019 some of the local community in Kalibenda Village have experienced difficulties in accessing clean water supply which has never happened in the past . This study provides an analyze of the impact of land use changes that occur in Kalibenda Village on surface runoff. This study uses a Rational method to calculating runoff discharge by using elevation profile analysis tool from Google Earth program to calculated sloop, Approb_4.1 program to process rain data and ArcSwat Tools in the ArcMap 10.2 program to water catchment analysis. The study results shows that Kalibenda Village divided into 6 (six) catchment water. There has been increased runoff from 2000 to 2021 by 6.44%. The most influential factors are changes in land cover change from rice fields to settlements, plantations and meadow grass.